Genetic assessment of the invasion history of Drosophila suzukii in Argentina - De La Vega, Gerardo; Corley, Juan Carlos; Soliani, Carolina (Springer Nature, 2019)
Drosophila suzukii (Diptera: Drosophilidae) is a highly polyphagous fruit pest native to eastern Asia, which in the last decade had widely expanded its range and become a serious pest in the Americas and Europe. Invasion routes and the genetic diversity in populations of South America are poorly studied. Here, we compared the patterns of genetic variation of native populations and previously invaded regions (in America and Europe) with the genetic diversity of the recent invasion in Argentina. In addition, we explored the regional trade routes and volume of host fruits (Argentina, Brazil, Chile and Uruguay) to understand propagule pressure. We report for the first time a genetic assessment of the invasion history of D. suzukii in Argentina, noting genetic diversity at Cytochrome c oxidase subunit I gene fragment comparable with other recently colonized countries. In the years prior to the invasion into South America, Brazil imported large quantities of potential host fruits from different countries that had been previously invaded; likely Brazil might be the main source of D. suzukii in Argentina. This is emphasized by the fact that Argentina and Brazil share haplotypes; however, direct commercial pathway with the USA cannot be discarded, and additional sources of species arrivals are also possible. Our results suggest at least two invasion events could have occurred in Argentina, originating both from previously invaded areas (i.e., North America and Brazil). Our study provides information to improve our understanding of the routes and factors affecting the invasion of this economically significant pest in South America.